METODE DISKUSI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VB SDN 007 PANIPAHAN - Sudarmiati, Sudarmiati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The background of this research is teaching and learning process in class V SDN 007 Panipahan in IPS subjects which is still dominated by teachers so that students become passive receive just the material given by the teacher and the learning result which not yet satisfy with the mean value under KKM. This study aims to determine whether there is influence of discussion methods, both individually and classically to the results of class V B on the subject of social studies in SDN 007 Panipahan. The study was conducted on 32 students consisting of 20 men and 12 women. Data were collected through observation by observer using observation sheet for discussion method data, and through postes unutuk data learning result. The results showed that the method of discussion can improve student learning outcomes, this is evidenced by: Student learning outcomes have increased, in the cycle I average learning outcomes obtained by students is 70.78. In the second cycle has increased with average learning outcome of 75.31. In addition, the classical completeness also increased on the percentage prasiklus student klasiskal completeness of 56.25%, in the first cycle reached 68.75%, in cycle II classical completeness reached 87.53%.